2014
DOI: 10.1103/physreve.89.042201
|View full text |Cite
|
Sign up to set email alerts
|

Impact dynamics of granular jets with noncircular cross sections

Abstract: Using high-speed photography, we investigate two distinct regimes of the impact dynamics of granular jets with non-circular cross-sections. In the steady-state regime, we observe the formation of thin granular sheets with anisotropic shapes and show that the degree of anisotropy increases with the aspect ratio of the jet's cross-section. Our results illustrate the liquid-like behavior of granular materials during impact and demonstrate that a collective hydrodynamic flow emerges from strongly interacting discr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, when investigating the impact between two free streams or objects, it is natural to simplify the dynamics by fixing the first object and then collide the second against the first. Examples where this has has been done when studying the off-center collision of granular streams [27] or the formation of protoplanets [32][33][34]. However, because of the presence of central drift in dense, dissipative impacts, the outcome of collisions when fixing one object is fundamentally different than the free-collision counterpart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, when investigating the impact between two free streams or objects, it is natural to simplify the dynamics by fixing the first object and then collide the second against the first. Examples where this has has been done when studying the off-center collision of granular streams [27] or the formation of protoplanets [32][33][34]. However, because of the presence of central drift in dense, dissipative impacts, the outcome of collisions when fixing one object is fundamentally different than the free-collision counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Comoving reference frame The collision produces some familiar behavior, namely that two collimated ejecta streams are produced as in the case of impact against a fixed target [7,11,12,27]. The collimated ejecta are traveling with velocity U out at an angle Ψ 0 relative to the horizontal.…”
Section: A Steady Saddle Driftmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellowitz investigated the head‐on impingement of dense granular jets with unequal‐width by discrete particle simulations, and the shift of impact stagnation point was revealed due to the dissipation. Note that the particle behaviors of a dense granular jet impacting on a solid target were experimentally studied by Cheng et al They found that as the number of particles in the jet decreases, a liquid‐like granular sheet changes to a diffuse pattern due to rapid interparticle collisions during impact of the target. Their results also imply that the impingement of two dense granular jets may give rise to the granular sheet, but detailed experimental result has not been presented and collision‐level information is not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…The second similarity concerns the interaction of a granular jet with a solid obstacle, e.g. 7 8 9 10 11 12 where granular sheets or cone-like structures emerge. This behavior corresponds to Savart water bells observed for fluid jets 13 14 .…”
mentioning
confidence: 99%